Reproductive biology of Philodryas patagoniensis (Snakes: Dipsadidae) in south Brazil: Female reproductive cycle. (20th June 2017) - Loebens, Luiza; Rojas, Claudio Augusto; Almeida‐Santos, Selma Maria; Cechin, Sonia Zanini
Abstract: In this study, we describe the female reproductive cycle of Philodryas patagoniensis in south Brazil, which was described through morpho‐anatomical and histological analyses. The peak of secondary vitellogenesis occurred during winter–spring (July–December), ovulation in spring (October–December), mating and fertilization in spring–summer (October–February), oviposition in spring–autumn (October–May) and births from late spring to autumn (December–July). The diameter of vitellogenic follicles/eggs was larger in winter–spring than in other seasons. The diameter of the shell glands was also larger in winter–spring. In spite of the clear reproductive peak, gonads only showed reduced activity in the autumn. Therefore, at the individual level, females have a discontinuous cyclical reproduction; in the populational level, the reproductive cycle is seasonal semisynchronous. We support the hypothesis that P. patagoniensis have the ability to produce multiple clutches with long‐term stored sperm. Sexual dimorphism in body size was evident, and females are significantly larger and heavier than males. Larger females were able to produce follicles and eggs in larger amount and size. The maternal body size was positively related to the reproductive effort and fecundity. To conclude, we deliberated about the proximal and distal causes that influence the reproductive traits and patterns of P. patagoniensis .